2019
DOI: 10.1186/s13104-019-4756-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased PTEN gene expression in patients with endometrial carcinoma from areas of high risk depleted uranium exposure

Abstract: ObjectiveInvestigate PTEN gene expression and tumor aggressiveness in endometrial carcinoma specimens from patients living in either areas of depleted uranium [DU] pollution or unpolluted regions to determine any evidence for the effect of war pollution on the rising trends of cancer incidence in Iraq.ResultsTumor PTEN gene expression was significantly increased in patients living in the areas of high risk DU exposure, in comparison to patient tumors from low risk areas [P = 0.001]. The age distribution betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…EC is the most common gynecologic malignancy in the western world [ 2 , 3 , 34 ], and survival rates are not improving. There is urgent need for strategies to improve outlook for patients with aggressive subtypes and advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…EC is the most common gynecologic malignancy in the western world [ 2 , 3 , 34 ], and survival rates are not improving. There is urgent need for strategies to improve outlook for patients with aggressive subtypes and advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2A gene locus encodes two tumor suppressor proteins p16/INK4A and P14/ARF, which regulate cell cycle by cyclin D inhibition, and its inactivation leads to a tumorigenesis through the PI3K/Akt pathway [ 44 ]. Recent studies provide evidence of PI3K and MAPK pathways' involvement in uranium-induced toxicity [ 45 , 46 ]. In addition, the activation of the NF-κB/IL-6 pathway in response to INK4a/ARF inhibition triggering tumor growth and development has been described recently [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single study measured the expression of the tumour-suppressor gene, PTEN, in endometrial carcinoma patients living in DU-exposed areas (cases) and unexposed areas (controls) in Southern Iraq. 53 The study found that PTEN gene expression mean fold change was greater among the exposed group (0.139±0.185) than the unexposed group (0.0031±0.0029), but the difference in means was not statistically significant when tumour grade and cancer stage were controlled for (p=0.286 and p=0.98, respectively).…”
Section: Resultsmentioning
confidence: 91%